Suspected Spontaneous Aqueous Humor Misdirection Syndrome in a Boston Terrier - Ashley E. Zibura; Michael G. Davidson; Hans D. Westermeyer (Case Reports in Veterinary Medicine)
An eight-year-old female spayed Boston Terrier presented to the North Carolina Veterinary Hospital with glaucoma in the left eye (OS). Initial ophthalmic examination revealed moderate ocular hypertension, a diffusely and markedly shallow anterior chamber with anteriorly displaced iris and lens, vitreal prolapse, and a normal iridocorneal angle (ICA) morphology. The patient displayed a paradoxical response to topical latanoprost with an increase in intraocular pressure. These examination findings led to a putative diagnosis of spontaneous aqueous humor misdirection syndrome (AHMS). The patient was successfully managed with topical carbonic anhydrase inhibitors (CAIs) and apraclonidine for eight months until progressive ulcerative keratitis necessitated enucleation of the affected globe. Histopathology and high-field magnetic resonance imaging (MRI) of the enucleated globe did not identify an underlying cause for the glaucoma. This case suggests that AHMS should be considered in dogs presenting with a shallow anterior chamber, vitreal prolapse, increased intraocular pressure, and no other causes of glaucoma.